Evaluation of the Pediatric Neuro-Oncology Resources Available in Chile. (2021) - Abu-Arja, Mohammad H.; Rojas del Río, Nicolás; Morales La Madrid, Andres; Lassaletta, Alvaro; Coven, Scott L.; Moreno, Rosa; Valero, Miguel; Perez, Veronica; Espinoza, Felipe; Fernandez, Eduardo; Santander, José; Tordecilla, Juan; et al.
Abstract : PURPOSE: Pediatric neuro-oncology resources are mostly unknown in Chile. We report the human and material resources available in Chilean hospitals providing pediatric neuro-oncology services. METHODS: A cross-sectional survey was distributed to 17 hospitals providing pediatric neuro-oncology services (Programa Infantil Nacional de Drogas Antineoplásicas [PINDA] hospitals, 11; private, 6). RESULTS: Response rate was 71% (PINDA, 8; private, 4). Pediatric neuro-oncology services were mainly provided within general hospitals (67%). Registries for pediatric CNS tumors and chemotherapy-related toxicities were available in 100% and 67% of hospitals, respectively. CNS tumors were treated by pediatric oncologists in 92% of hospitals; none were formally trained in neuro-oncology. The most used treatment protocols were the national PINDA protocols. All WHO essential medicines for childhood cancer were available in more than 80% of the hospitals except for gemcitabine, oxaliplatin, paclitaxel, and procarbazine. The median number of pediatric neurosurgeons per hospital was two (range, 2-6). General neuroradiologists were available in 83% of the centers. Pathology specimens were sent to neuropathologists (58%), adult pathologists (25%), and pediatric pathologists (17%). Intensity-modulated radiotherapy, conformal radiotherapy, and cobalt radiotherapy were used by 67%, 58%, and 42% of hospitals, respectively. Only one private hospital performed autologous hematopoietic cell transplant for children with CNS tumors. CONCLUSION: A wide range of up-to-date treatment modalities are available for children with CNS tumors. Our survey highlights future directions to improve the pediatric neuro-oncology services available in Chile such as the expansion of multidisciplinary clinics, palliative care services, long-term cancer survivorship programs, dedicated clinical research support teams, establishing standardized mechanism for sending pathologic specimen for second opinion to international specialized centers, and establishing specialized neuro-oncology training program.